Influence of Moisture and Temperature Regimes on the Phytolith Assemblage Composition of Mountain Ecosystems of the Mid Latitudes: A Case Study From the Altay Mountains - Solomonova, Marina Y.; Blinnikov, Mikhail S.; Silantyeva, Marina M.; Speranskaja, Natalya Y. (Frontiers in Ecology and Evolution, 2019)
Reconstruction of past ecosystems requires robust understanding of modern deposition patterns and taphonomy for the proxy in question. In phytolith analysis, much has been achieved in this respect in the last 20 years. However, many gaps remain and this study aims to test a few specific hypotheses that have been proposed by research in Northern Hemisphere. Our study area is Northern Altay, entirely within Russia, north of China. We collected 60 phytolith assemblages from modern soils at 300 to 2300 m a.s.l. elevations from 20 plots in triple replicates within 13 different plant communities in the summer of 2017. Communities range from forests to meadows to steppe to alpine tundra. We use a locally derived scheme of Sedelnikov to assign studied communities to ecological categories based on moisture and temperature availability. Standard oxidation and heavy liquid flotation methods of extraction have been used. Morphotypes were counted under x400-x1000 magnification on an optical microscope. We use a two-tier approach to phytolith morphotypes classification: a detailed one with >50 morphotypes and a shorter one with only sums of selected morphotypes. In the former approach, some interesting results can be obtained, for example, with various types of rondels (pyramidal vs. keeled) or large vs. small lanceolate. At the same time, using sums may be easier because the researchers can replicate these results better and less training is needed. However, there are fewer diagnostic options with the sums approach. Our results using discriminant analysis, canonical correspondence analysis and other multivariate statistical methods confirm earlier studies in the region and elsewhere that while a lot of redundancy in phytolith distributions occur, there are some selected morphotypes that can reliably distinguish communities at various positions along moisture and temperature gradients. We developed a regionally diagnostic key that allows researchers to quickly identify various plant communities based on their phytolith assemblages in soils and derive some transfer functions to directly infer moisture and temperature regimes of the past based on phytolith records in soils. Seven of 13 regionally important communities at medium elevations can be distinguished based on phytolith analysis using aggregated and more detailed morphotypes.